Pengembangan Media DAKOTAR (Dakon Matematika Pintar) Materi Satuan Panjang dan Satuan Berat untuk Meningkatkan Keaktifan dan Kemampuan Berhitung Siswa Kelas IV di SDN Gogodeso 01 - Sayyidah Irma Sulkhana; Fathul - Niam; Ahmad - Saifudin (Lembaga Penelitian dan Pengabdian Masyarakat, Universitas Nahdlatul Ulama Blitar, 2022)
Abstract: Learning media is an intermediary tool to convey messages or learning materials used dby dteachers/educators dto dstudents dso dthat dthey dcan dattract dstudents' dattention, dthoughts dand dinterests dto dparticipate din dthe dlearning dprocess. dBased don dinterviews dthat dresearchers dconducted dwith dfourth dgrade dteachers dat dSDN dGogodeso dd01, ddthey ddfound ddproblems, ddnamely dd(1) ddlack ddof ddvariety ddof ddlearning ddmedia dd(2) ddteachers ddstill dduse ddthe ddlecture ddmethod ddin ddthe ddlearning ddprocess. ddThe ddpurpose ddof ddthis dddevelopment ddresearch ddis ddto ddproduce ddDAKOTAR ddmedia dd(Dakon ddMathematics ddPintar) ddclass ddIV ddat ddSDN ddGogodeso dd01. ddThis ddstudy dduses dd5 ddstages ddof ddthe ddADDIE ddmodel, ddnamely ddanalysis, dddesign, dddevelopment, ddimplementation, ddand ddevaluation. ddData ddcollection ddtechniques ddused ddin ddthe ddform ddof ddquestionnaires, ddtests ddand dddocumentation. ddThe dddata ddcollection ddinstruments ddused ddwere ddquestionnaires ddfor ddmaterial ddexperts ddand ddmedia ddexperts ddas ddwell ddas ddactivity ddquestionnaires ddand ddtests ddfor ddstudents. ddThe ddresults ddof ddthis ddstudy ddinclude ddmaterial ddexpert ddvalidation, ddobtained dda ddpercentage ddof dd86% ddwith ddvery ddvalid ddcriteria ddwithout ddrevision ddand ddmedia ddexpert ddvalidation ddobtained dda ddpercentage ddof dd81% ddwith ddfairly ddvalid ddcriteria ddwith ddslight ddrevisions, ddthe ddresults ddof ddthe ddstudent ddactivity ddtest ddget dda ddscore ddof dd85.7% ddwith ddvery ddactive ddcategory. ddDAKOTAR dd(Dakon ddMathematics ddPintar) ddfor ddincreasing ddnumeracy ddskills ddfor ddclass ddIV ddis ddcategorized ddas ddhaving dda ddmoderate ddincrease ddwith ddan ddoverall ddN-Gain ddscore ddof dd0.37. ddSo ddthe dddevelopment ddof ddDAKOTAR dd(Dakon ddMathematics ddPintar) dis dvalid dand dcan dincrease dstudents' dactiveness dand dnumeracy dskills.